Partial discharge signal pattern analysis in frequency domain - Noraniza Binti Hamrie (2023)
This project report comprises of my study on Partial Discharge Signal Pattern Analysis in Frequency Domain. I have done literature survey regarding Partial Discharge (PD) Phenomena in XLPE cable. PD data were obtained under three different soil thermal resistivities and cable loading to acquire "Electrical PD Signal" in the shape of ellipse on a 50Hz time base. PD elliptical waveform sampled to represent PD in 2D graph of charge (pC) vs (ms), then we obtained a time domain graph. The time domain electrical PD signals are then filtered using Matlab Simulink Block to obtain the filtered time domain graph.